2022
DOI: 10.1111/nmo.14345
|View full text |Cite
|
Sign up to set email alerts
|

FODMAP dietary restrictions in the management of children with functional abdominal pain disorders: A systematic review

Abstract: The available nutritional interventions for the management of functional abdominal pain disorders (FAPD) in children are limited. 1,2 Evidence of the efficacy of implementing a diet low in fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAPs) is limited. 2 The rationale for use of a low-FODMAP diet is based on the assumption that a decrease in the short-chain fermentable carbohydrate load, both, prevents the osmotic effect of FODMAPs, resulting in a decrease in small intestine wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In accordance with the present study, one previous relevant systematic review of RCTs [81] concluded that there are several methodological limitations of the available clinical trials on the efficacy of using a low-FODMAP diet in the treatment of children with FGIDs. Researchers concluded that the choice of the comparator diet (usually a non-standardized treatment for children with FGIDs compared to a placebo diet that is considered the gold standard method) as well as other domains (e.g., the success of blinding after follow-up, the carryover effects in crossover studies, the optimal duration of intervention) carried with them a high risk of bias [81].…”
Section: Literature Documentionsupporting
confidence: 88%
“…In accordance with the present study, one previous relevant systematic review of RCTs [81] concluded that there are several methodological limitations of the available clinical trials on the efficacy of using a low-FODMAP diet in the treatment of children with FGIDs. Researchers concluded that the choice of the comparator diet (usually a non-standardized treatment for children with FGIDs compared to a placebo diet that is considered the gold standard method) as well as other domains (e.g., the success of blinding after follow-up, the carryover effects in crossover studies, the optimal duration of intervention) carried with them a high risk of bias [81].…”
Section: Literature Documentionsupporting
confidence: 88%
“…There are special considerations to make when treating adolescents with comorbid CFAP and restrictive EDs. CFAP patients are asked to make dietary changes in order to avoid foods that trigger gastrointestinal distress, such as adopting a low FODMAP diet [ 65 , 84 ]. However, within the context of restrictive EDs, clinicians may need to approach recommendations for dietary changes with caution.…”
Section: Recommendations For Treatment Of Cfap and Restrictive Edsmentioning
confidence: 99%
“…Three randomised control trials, one prospective observational study and one retrospective evaluation, all from different countries, as detailed in Table 1 [ 27 , 32 , 33 , 34 , 35 ], suffered from major limitations of trial design and/or reporting that included underpowering, a short duration of dietary intervention, poor assessment of dietary compliance and actual FODMAP intake, and for some, overinterpretation of pilot data. The designs and targeted populations are too heterogenous to be subjected to meta-analysis, but authors systematically reviewing the data have consistently concluded that efficacy of the low FODMAP diet in children is uncertain, but there are sufficient signals to warrant further studies of better quality [ 36 , 37 , 38 ]. A recent position statement by ESPGHAN concluded that there is scarce evidence to support the use of a low-FODMAP diet in children with IBS [ 39 ].…”
Section: Efficacy Of the Fodmap Diet In Paediatric Ibsmentioning
confidence: 99%